Subgroup analyses with special reference to the effect of antiplatelet agents in acute coronary syndromes - Aronson, Doron (Thrombosis and Haemostasis, 2014)
Controlled trials estimate treatment effects averaged over the reference population of subjects. However, physicians are interested in whether the treatment effect varies across subgroups (effect heterogeneity) in order to target specific subgroups to maximise the benefit of treatment and minimise harm. Therefore, large clinical trials of antiplatelet agents include subgroup analyses that examine whether treatment effects differ between subgroups of subjects identified by baseline characteristics. Reporting subgroup is pervasive and often accompanied by claims of difference of treatment effects between subgroups with potential important implications for clinical practice. However, subgroup-specific analyses of clinical trial data have inherent limitations that reduce their reliability. These include reduced statistical power, failure to specify the subgroups of interest a priori, failure to account for examining large numbers of subgroups, lack of strong rationale for biological response modification, and performing analyses based on variables measured post randomisation or in trials showing no overall difference between treatments. Rules for interpretation of subgroup findings in subgroups have been suggested but are frequently not applied. In this article we draw attention to the pitfalls of subgroup analyses in the context of recent trials of antiplatelet agents.
Keywords: Clinical trials; effect modification; interaction; prasugrel; statistics; subgroup analysis; ticagrelor